Integrated design for large-scale opto-mechanical structure - Li, Anhu; Bian, Yongming; Liang, Yongcheng; Zhu, Yongjian (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
An integrated design method is discussed which thoroughly considers related parameters of the various subsystems in order to optimize the overall system that mainly consists of opto-mechanical structure CAD, CAE and the integrated information platform PDM. Based on the parameter drive of the virtual main model, the method focuses on the model transformation and data share among different design and analysis steps, and so the concurrent simulation and design optimization are carried out. As an example of application, the integrated design for a large-scale opto-mechanical structure is introduced, including optical design, structure design and analysis, which further validates the advantages of the method. Due to comprehensive consideration of the design and analysis process by CAD and CAE based on PDM, the integrated design well attains the structure optimization with high efficiency.
Optica Applicata, Vol. 39, 2009, nr 2, s. 383-389
Keywords: optyka; integrated design; CAD/CAE; large-scale structure; optical instrument